2020
DOI: 10.1097/mcg.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 is Elevated in Eosinophilic Esophagitis but Not in Gastroesophageal Reflux Disease Patients

Abstract: Background: For eosinophilic esophagitis (EoE) recently an association with immunoglobulin (Ig)G4 rather than IgE has been reported. Gastroesophageal reflux disease (GERD) is the most important differential diagnosis of EoE. We compared esophageal IgG4 plasma cell infiltration and serum IgG4 levels of EoE patients (before and after budesonide therapy) with GERD patients. Methods: Prospectively collected serum samples of 17 EoE patients before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 27 publications
4
31
0
2
Order By: Relevance
“…14 Thus, EoE is hypothesized to be associated with IgG4 and not related to IgG4. 14 We observed that IgG4 staining was able to distinguish between EoE and GERD with a moderate sensitivity of 77% and a high specificity of 93%. This is similar to a study that showed a sensitivity and specificity of 88% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…14 Thus, EoE is hypothesized to be associated with IgG4 and not related to IgG4. 14 We observed that IgG4 staining was able to distinguish between EoE and GERD with a moderate sensitivity of 77% and a high specificity of 93%. This is similar to a study that showed a sensitivity and specificity of 88% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…5,6 Our results suggest that IgG4 staining can be used as an adjunct to help differentiate between EoE and GERD as previously proposed. 14 This is the first study to our knowledge that has shown positive IgG4 staining in the GERD cohort (7% [2/30]). These two patients have been confirmed, on repeat examination of their medical records, to not meet criteria for a diagnosis of EoE.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…EoE has not been shown to be influenced by immunoglobulin E (IgE)[25]; however, an increase in IgG4 has been found in tissue samples, and IgG4 specific to some SFED food allergens has been found in serum samples[26,27], which supports the theory that EoE is truly an IgG4-mediated disease. In clinical practice, immunostaining for IgG4 in esophageal biopsies has not been effective in diagnosing EoE, as it has a low sensitivity of 48%[28].…”
Section: Immunogenetic Factorsmentioning
confidence: 91%